2006
DOI: 10.1002/jnr.21045
|View full text |Cite
|
Sign up to set email alerts
|

Altered gene activity correlated with long‐term memory formation of conditioned taste aversion in Lymnaea

Abstract: The pond snail Lymnaea stagnalis is capable of learning conditioned taste aversion (CTA) and then consolidating that learning into long-term memory (LTM) that persists for at least 1 month. LTM requires de novo protein synthesis and altered gene activity. Changes in gene activity in Lymnaea that are correlated with, much less causative, memory formation have not yet been identified. As a first step toward rectifying this situation, we constructed a cDNA microarray with mRNAs extracted from the central nervous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 58 publications
2
46
0
Order By: Relevance
“…Kojima et al (1997) showed that activity in the CGC caused a large and long-lasting polysynaptic inhibitory effect on the N1M cell, which is one of the feeding central pattern generator neurons, in snails exhibiting CTA-LTM. This can be explained by action of the cAMP-protein kinase A (PKA)-cAMP response element-binding protein (CREB) pathway in the CGC (Nakamura et al, 1999b;Sadamoto et al, 2004Sadamoto et al, , 2010Sadamoto et al, , 2011Wagatsuma et al, 2005Wagatsuma et al, , 2006. These results suggest that CGC-B1 synapses serve as a good model in which to elucidate how changes in synaptic transmission amplitude, for example, serve as a neural correlate of behavioral memory.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kojima et al (1997) showed that activity in the CGC caused a large and long-lasting polysynaptic inhibitory effect on the N1M cell, which is one of the feeding central pattern generator neurons, in snails exhibiting CTA-LTM. This can be explained by action of the cAMP-protein kinase A (PKA)-cAMP response element-binding protein (CREB) pathway in the CGC (Nakamura et al, 1999b;Sadamoto et al, 2004Sadamoto et al, , 2010Sadamoto et al, , 2011Wagatsuma et al, 2005Wagatsuma et al, , 2006. These results suggest that CGC-B1 synapses serve as a good model in which to elucidate how changes in synaptic transmission amplitude, for example, serve as a neural correlate of behavioral memory.…”
Section: Methodsmentioning
confidence: 99%
“…The existence of activator and repressor types of CREB, CREB1 and CREB2, has also been demonstrated in the CGCs and other neurons (Ribeiro et al, 2003;Sadamoto et al, 2004Sadamoto et al, , 2010Sadamoto et al, , 2011Wagatsuma et al, 2005Wagatsuma et al, , 2006. Moreover, prior injection of the CRE oligonucleotide or a PKA inhibitor into the CGC blocked the expression of this long-lasting change in synaptic plasticity at the CGC-B1 synapses (Nakamura et al, 1999b;Sadamoto et al, 2004).…”
Section: Possible Function Of Mips In a Long-term Synaptic Enhancementmentioning
confidence: 96%
See 2 more Smart Citations
“…Our group has primarily focused our attention on conditioned taste aversion (CTA) in this model system (Kojima et al, 1996). We previously found that molluscan insulin-related peptides (MIPs) were upregulated in snails exhibiting CTA (Azami et al, 2006). More recently, we have shown at the electrophysiological level that application of mammalian insulin or MIPs to the isolated central nervous system (CNS) evoked long-term synaptic enhancement at the serotonergic excitatory monosynaptic connection between the cerebral giant cell (CGC) and the buccal 1 (B1) motor neuron (Murakami et al, 2013).…”
Section: Introductionmentioning
confidence: 99%